Effects of Responsiveness, Professionalism, Informativeness, and Personalization on Purchase Intentions Via Product Trust in Skintific Shopee Livestream - Nabila Saharani; Erlita Ridanasti (Universitas KH. Abdul Chalim Mojokerto, 2025)
The popularity of live streaming features in the e-commerce industry is steadily increasing and has become one of the most favored marketing strategies, as it facilitates two-way communication between streamers and consumers. Through this interaction, consumers not only receive product information but also develop perceptions, enhance trust, and eventually form purchase intentions. This study aims to examine how communication elements in live streaming influence consumer trust in products and their intentions to make continuous purchases. The theoretical framework employed in this research is the Stimulus Organism Response (S-O-R) Theory. A quantitative research method was applied using purposive sampling, involving 186 respondents who had purchased Skintific products through Shopee’s live streaming feature. Data were collected through an online questionnaire distributed via Google Forms and analyzed using SPSS and Partial Least Square Structural Equation Modeling (PLS-SEM). This study investigated six main variables: responsiveness, professionalism, informativeness, personalization, product trust, and continuous purchase intention. The results revealed that responsiveness, professionalism, and informativeness had positive effects on product trust. Furthermore, product trust was found to have a significant and positive impact on continuous purchase intention. Conversely, personalization did not show a meaningful effect on either product trust or purchase intention.